Reduced between-hospital variation in short term survival after acute myocardial infarction: the result of improved cardiac care?. Issue 6 (13th May 2005) - Murphy, N F; MacIntyre, K; Stewart, S; Capewell, S; McMurray, J J V
Abstract : Objectives: To re-examine interhospital variation in 30 day survival after acute myocardial infarction (AMI) 10 years on to see whether the appointment of new cardiologists and their involvement in emergency care has improved outcome after AMI. Design: Retrospective cohort study. Setting: Acute hospitals in Scotland. Participants: 61 484 patients with a first AMI over two time periods: 1988–1991; and 1998–2001. Main outcome measures: 30 day survival. Results: Between 1988 and 1991, median 30 day survival was 79.2% (interhospital range 72.1–85.1%). The difference between highest and lowest was 13.0 percentage points (age and sex adjusted, 12.1 percentage points). Between 1998 and 2001, median survival rose to 81.6% (and range decreased to 78.0–85.6%) with a difference of 7.6 (adjusted 8.8) percentage points. Admission hospital was an independent predictor of outcome at 30 days during the two time periods (p < 0.001). Over the period 1988–1991, the odds ratio for death ranged, between hospitals, from 0.71 (95% confidence interval (CI) 0.58 to 0.88) to 1.50 (95% CI 1.19 to 1.89) and for the period 1998–2001 from 0.82 (95% CI 0.60 to 1.13) to 1.46 (95% CI 1.07 to 1.99). The adjusted risk of death was significantly higher than average in nine of 26 hospitals between 1988 and 1991 but in only two hospitals between 1998 and 2001. Conclusions: The average 30 day case fatality rate after admission with an AMI has fallen substantially over the past 10 years in Scotland. Between-hospital variation is also considerably less notable because of better survival in the previously poorly performing hospitals. This suggests that the greater involvement of cardiologists in the management of AMI has paid dividends.